Exploring the Enabling Mechanism and Implementation Path of Digital Economy on High-Quality Development in Tourism: A Case Study of Shanghai Disney Resort - Chen, Chiu-Mei; Li, Jie; Li, Hsuan (Journal of China-ASEAN Studies, 2024)
With the in-depth development of the digital era, the close integration of the digital economy and tourism is leading the tourism industry into a new stage of development. This paper examines the theoretical framework and future development trends of the integration of digital economy development and tourism, and clarifies the complementary and synergistic relationship between them. Through intelligent service innovation, refined management optimization, and personalized experience enhancement, the digital economy has played a crucial role in promoting high-quality growth in tourism. With empirical case studies, this paper delves into the practical applications and effectiveness of digital technology in tourism, revealing how digitalization has made tourism destination promotion more precise and efficient, tourism services more convenient and speedy, and tourism experiences more diverse and enriching. At the same time, digital tourism has significantly improved the operational efficiency and management level of the tourism industry, laying a solid foundation for its sustainable development. Nevertheless, the development of the digital economy also brings many challenges and risks. To this end, this paper proposes a series of targeted strategic suggestions, including improving digital infrastructure in the tourism industry, enhancing the digital skills of practitioners, and strengthening data security and privacy protection, to ensure the steady progress of the tourism industry. In the future, with the further penetration of the digital economy, it is expected to continue driving the tourism industry towards higher levels of sustainable development. Therefore, paying attention to and addressing the challenges and risks brought by the digital economy, strengthening regulation and standardization, is crucial to ensuring that the digital economy plays a positive role in promoting the development of the tourism industry.